THE HIGH-QUALITY OF CLINICAL PRACTICE EVALUATION FOR NURSING STUDENTS: A LITERATURE REVIEW - Saputra, Muhamad Andika Sasmita; Sansuwito, Tukimin Bin; Said, Faridah Mohd (Citra Internasional Institute, 2024)
Background: Evaluation processes of clinical practice among nursing students can be less than optimal due to individual, organizational, and psychological factors. Improving clinical practice evaluations enhances student outcomes. Therefore, to measure quality in these evaluations, it is essential to identify standard components for evaluating clinical practice quality among nursing students. Purpose: This literature review aims to analyse what components influence the quality of clinical practice evaluation among nursing students. Methodology: The literature review is done by taking electronic database sources through e-book and journal search engines, such as Google Book, Google Scholar, Pro-Quest, PUBMED, and Science Direct. The criteria for published books are the last ten years (2013-2023) and journals for the last five years (2018-2023) using the keywords